Metabolic Changes in Occipital Lobe Epilepsy with Automatisms - Wong, Chong H.; Mohamed, Armin; Wen, Lingfeng; Eberl, Stefan; Somerville, Ernest; Fulham, Michael; Bleasel, Andrew F. (Frontiers in Neurology, 2014)
Purpose: Some studies suggest that the pattern of glucose hypometabolism relates not only to the ictal-onset zone, but also reflects seizure propagation. We investigated metabolic changes in patients with occipital lobe epilepsy (OLE) that may reflect propagation of ictal discharge during seizures with automatisms. Methods: Fifteen patients who had undergone epilepsy surgery for intractable OLE and had undergone interictal Fluorine-18-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) between 1994 and 2004 were divided into two groups (with and without automatisms during seizure). Significant regions of hypometabolism were identified by comparing 18F-FDG-PET results from each group with 16 healthy controls by using Statistical Parametric Mapping (SPM 2). Key Findings: Significant hypometabolism was confined largely to the epileptogenic occipital lobe in the patient group without automatisms. In patients with automatisms, glucose hypometabolism extended from the epileptogenic occipital lobe into the ipsilateral temporal lobe. Significance: We identified a distinctive hypometabolic pattern that was specific for OLE patients with automatisms during a seizure. This finding supports the postulate that seizure propagation is a cause of glucose hypometabolism beyond the region of seizure onset.